(untitled) (Research, Society and Development, 2022)
Obstetric violence is understood as any act of violence practiced by health professionals against women during prenatal care, childbirth and/or puerperium that inflict physical, psychological and/or social suffering on them. Occurrences of cases of obstetric violence range from offensive comments to misappropriation of the woman’s body and reproductive processes in the situations described above. In this sense, this study aims to be a source of knowledge and information, through health education about obstetric violence in the contemporary setting of childbirth care in Brazil. Therefore, a study was carried out in the form of an integrative bibliographic review of the literature in Scientific Electronic Library Online (Scielo), LatinAmerican and Caribbean Literature in Health Sciences (LILACS) and Virtual Health Library (VHL) databases, using the Health Descriptors (DECS) Violence and Obstetric and Part. For this, articles that portrayed the contextualization of Obstetric Violence, the types of violence and violence from the perspective of women were approached. Thus, there needs to be a reform in the care provided, based mainly on humanization, respecting women’s autonomy so that they feel protagonists of this moment.